Irish Studies at the National University of La Pampa, Argentina: a Review. - Eliggi, María Graciela; Obert, Graciela; Alfonso, Norma L; Basabe, Enrique A (ABEI Journal, 2017)
“Literaturas Contemporáneas en Diálogo” is an ongoing ResearchProgramme1 (2015-2023) that evolved from previous work carried out in the field of Comparative Literature in English and in Spanish, and as a resultof research done in two previous projects related to Irish Literature, namely“Irlandeses en Argentina: recuperación de fuentes, traducción y crítica”(2007-2010) and “Las Américas e Irlanda: Estudios culturales y traducción”(2011-2014).